Telling stories between fairy tales and Storytelling: a concept of valuing, understanding, and enjoying learning through a model of telling stories in the context of the Qur'an - Mohammad Badru Tamam (PROGRESSA: Journal of Islamic Religious Instruction, 2019)
Fairy tale in the sense of fiction / fiction telling stories, such as: fable, sage, saga, legend, mythe, ephos. Telling stories are interpreted as narrations about events. Fairy tale delivered continuously will be boring, over time the audience is not enthusiastic about listening. Telling stories in fairy talekan differ in taste if they are equipped with movements that reflect the roles and character of characters who are refined talekan, in this case termed storytelling. The purpose of this article is to examine the concepts of fairy tale, telling stories and storytelling and the Qur'an about respecting, understanding, and enjoying learning through this model of telling stories. The conclusions of this article are: 1) Telling stories do not use improvisation, fairy tale improvisation in several parts, Storytelling uses the totality of improvisation; 2) Mastering the technique of menfairy tale, telling stories & storytelling well, educators have the opportunity to explore the potential intelligence, emotional and spiritual intelligence; 3) The Qur'an alludes to, but does not teach fairy tale, not even fable perspectives, but teaches stories and parables which in this context are amtsaal.